Evaluation of serum Asymmetric Dimethyl Arginine concentrations in coronary artery disease patients without traditional cardiovascular risk factors - Ghayour-Mobarhan, Majid; Ayati, Nayyereh; Sahebkar, Amirhossein; Moohebati, Mohsen; Ayati, Narjes; Elyasi, Sepideh; Mohammadpour, Amir Houshang (Acta Biomedica Atenei Parmensis, 2018)
Background: Previous studies have shown that Asymmetric Dimethyl Arginine (ADMA) is increased significantly during coronary artery diseases (CAD). However it is not clear either this increase is due to cardiovascular disease (CVD) risk factors or ADMA is increased independently in CAD. The aim of this study is to evaluate ADMA’s plasma level as an independent biomarker in CADs. Patients and methods: In current study a total of 165 subjects with no traditional CVD’s RFs, who fulfilled the inclusion and exclusion criteria, were recruited; 55 CAD+ patients which had more than 50% stenosis (CAD+); 55 CAD- patients which had less than 50% stenosis in their coronary arteries (CAD-), based on their angiography record and 55 healthy individuals as controls. CAD+ patients were divided into three groups: single (SVD), double (2VD), and triple vessel (3VD) disease. Plasma level of soluble ADMA was measured with an enzyme-linked immono sorbent assay (ELISA) kit. Results: No significant difference between ADMA’s plasma levels was found between CAD+, CAD- and healthy groups. In addition ADMA’s plasma levels was not significantly different between CAD+’s subgroups. Conclusions: The result of this study indicates no significant relation between ADMA’s plasma levels and either presence or severity of coronary artery stenosis. Therefore, it is presumed that ADMA may not be an independent biomarker for CADs.